PMO-196 Reducing time to gastroscopy in upper gastrointestinal bleeding. (28th May 2012) - Wong, M T; Sundaralingam, A; Bains, S; Shaw, K; Afghan, S; Filson, S A; Gooding, I
Abstract : Introduction: Approximately 300–350 patients present to Colchester General Hospital with an upper Gastrointestinal (GI) bleed per year. Guidelines advise endoscopy within 24 h of presentation. To improve our performance, we introduced a new system for prioritising these requests and monitored the results with repeated audits. Methods: An audit of all upper GI bleed cases was conducted over the same 3-month period (March–May) in 2009, 2010 and 2011. For each case we obtained the times of admission, Oesophagogastroduodenoscopy (OGD) request, procedure and discharge. The discharge summary, and where necessary the notes, were consulted to separate cases admitted for bleeding from those where bleeding occurred after admission for another reason. The main theatre logs were consulted for numbers of emergency out-of-hours OGDs. In an effort to tackle to poor waiting times, the Early Morning Bleeder (EMB) system was introduced in July 2009. Two slots are allocated daily (excluding weekends) for gastroscopy for cases of upper GI bleeding at the beginning of the working day. Requests are collected in a box in the Medical Assessment Unit daily at 0730. The Rockall Score is used for prioritisation. These three audits thus compare the situation before and after introducing the EMB system. Results: 2009 2010 2011 Total cases 72 80 85 Bleeder admissions 54 59 53 Wait from 0 3.7% 11.9% 15.1% admission to 1 29.6% 35.6% 49.1% OGD (days) ≥2 68.5% 52.5% 35.8% Mean wait for OGD (days) 3.26 1.95* 1.66* Median length of stay (days) 6 4 3* * p<0.05 compared to 2009. Waits were significantly longer for cases admitted on Friday or Saturday. Numbers of out of hours OGDs for bleeding were 12 (2007) and 11 (2008) before the EMB and 7 (2010) and 6 (2011) afterwards. Conclusion: The EMB system has reduced waits from presentation to OGD and length of hospital stay for patients presenting with upper GI bleeds. Patients are probably safer as the number of out of hours OGDs has fallen. There are plans to extend the service to include weekends. Hospitals with no current method for prioritising OGDs for bleeding should consider using this system. Competing interests: None declared.